2012
DOI: 10.1007/s00417-012-2044-2
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of lamellar macular holes: a spectral domain optical coherence tomography study

Abstract: Lamellar macular holes seem to be a stable macular condition. Vitrectomy should be considered only in the presence of progressive thinning of foveal thickness and/or decrease of visual acuity during the follow-up of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
125
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(138 citation statements)
references
References 20 publications
8
125
1
4
Order By: Relevance
“…Also, LMH floor thickness seems to be thinner in LHEP eyes ( p = 0.018) when compared to that of the non-LHEP LMH group, a result that is in agreement with findings from previous studies [13, 17, 19]. Our case series did not find any differences regarding the aperture of the LMH between the 2 groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, LMH floor thickness seems to be thinner in LHEP eyes ( p = 0.018) when compared to that of the non-LHEP LMH group, a result that is in agreement with findings from previous studies [13, 17, 19]. Our case series did not find any differences regarding the aperture of the LMH between the 2 groups.…”
Section: Discussionsupporting
confidence: 92%
“…LHEP were initially described as a “thick ERM” [5, 19]. However, their SD-OCT features did not resemble conventional ERM [11], and the clinical implications of this newly described material have been investigated since its first report.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, peeling of LHEP might be not as important for relieving epiretinal traction as peeling a standard ERM, but it would have the function of allowing surgical access to the ILM. The role of ILM as epiretinal material exerting traction in association with LMHs seems to be also confirmed by the fact that, as reported by previous studies, 5,12 and as observed in this series, full-thickness macular holes evolved from LMHs and associated with LHEP generally close after surgical removal of ILM.…”
Section: In This Retrospective Study We Show That In Eyessupporting
confidence: 90%
“…6,7,12 Blue fundus autofluorescence (B-FAF) imaging is a modality that relies on the fluorescence generated by the bisretinoids of lipofuscin in retinal pigment epithelial (RPE) cells and is influenced by absorbent or autofluorescent materials anterior to the RPE monolayer. 13,14 When imaged with B-FAF imaging, LMHs are characterized by an increased autofluorescent signal, the intensity of which does not correlate with the thickness of the residual outer retinal tissue.…”
mentioning
confidence: 99%
“…Visual acuity may be correlated with ERM type: A ERM is associated with lower visual acuity than C ERM. Figure 3a shows the comparison of BCVA between LMH associated with C ERM and LMH associated with A ERM ( p < 0.0001) [3, 4, 7-11, 22]. The difference in visual acuity may be explained by a greater involvement of outer intraretinal layers ( p = 0.0003) and of the ellipsoid zone and external limiting membrane (ELM), and by a lower residual foveal thickness in LMH associated with A ERM than in LMH associated with C ERM ( p = 0.00001) [3, 4, 8-10, 22] (Fig.…”
Section: Clinical Manifestationsmentioning
confidence: 99%